Surface Computing and Beyond: More Expressive Interaction - Hodges, Steve (Microsoft Research, 2008)
Surface Computing and Beyond: More Expressive Interaction. Slideshow.
Presentation at the UK-Japan HCI workshop held at the Bristish Embassy, Tokyo, Japan